Residual low HDV viraemia is associated HDV RNA relapse after PEG‐IFNa‐based antiviral treatment of hepatitis delta: Results from the HIDIT‐II study. (5th December 2020) - Bremer, Birgit; Anastasiou, Olympia E.; Hardtke, Svenja; Caruntu, Florin Alexandru; Curescu, Manuela G.; Yalcin, Kendal; Akarca, Ulus S.; Gürel, Selim; Zeuzem, Stefan; Erhardt, Andreas; Lüth, Stefan; Papatheodoridis, George V.; et al.
Abstract: The role of low levels of HDV‐RNA during and after interferon therapy of hepatitis D is unknown. We re‐analysed HDV RNA in 372 samples collected in the HIDIT‐2 trial (Wedemeyer et al, Lancet Infectious Diseases 2019) with the Robogene assay (RA; Jena Analytics). Data were compared with the previously reported in‐house assay (IA). We detected HDV‐RNA in one‐third of samples previously classified as undetectable using the highly sensitive RA. Low HDV viraemia detectable at week 48 or week 96 was associated with a high risk for post‐treatment relapse, defined as HDV RNA positivity in both assays at week 120. HDV RNA relapses occurred in 10/15 (67%) patients with detectable low HDV RNA at week 48 and in 10/13 (77%) patients with low viraemia samples at week 96. In contrast, the post‐treatment relapse rate was lower in patients with undetectable HDV RNA in both assays during treatment.